ANALISIS NILAI TOTAL SULFUR (TS) DAN CALORIFIC VALUE (CV) DALAM BATUBARA MENGGUNAKAN METODE AMRERICAN STANDARD TESTING AND MATERIAL (ASTM) DI PT GEOSERVICES SAMARINDA KALIMANTAN TIMUR - Novianti, Rina Lia; Sitorus, Saibun; Hiyahara, Irfan Ashari (PROSIDING SEMINAR KIMIA, 2024)
Coal is a crucial energy source with varying quality levels. It is formed by the accumulation of organic sediments mixed with carbon, resulting from the diagenesis process of plant elements. This study aims to determine the Total Sulfur (TS) and Calorific Value (CV) of coal, which are essential factors in assessing coal quality and economic value. The American Standard Testing and Material (ASTM) method is employed to ensure consistency and standardization in the analysis. From an analysis of six samples, the total sulfur content was determined to be 1.98% for sample A, 1.88% for sample B, 2.06% for sample C, 0.14% for sample D, 0.70% for sample E and 0.18% for sample F. Additionally, the calorific value were determined to be 6267 Cal/g for sample A, 6126 Cal/g for sample B, 6234 Cal/g for sample C, 5189 Cal/g for sample D, 4986 Cal/g for sample E and 3917 Cal/g for sample F. Based on the total sulphur analysis sample D, sample E and sample F can be used in the cement burning process because their total sulphur content is less than 0.8%. Meanwhile, based on the calorific value analysis sample A, sample B and sample C can be used the cement burning process because their calorific value above 6000 Cal/g. Keywords : Coal, total sulphur, calorific value, American Standard Testing and Material.